PAPALE: Langkah Cerdas Mahasiswa Mengelola Sitasi dan Referensi - Dwi Anggriani, Mitha; Indriani, Lina (Jurnal Pembelajaran dan Pengajaran Pendidikan Dasar, 2025)
Every student is required to produce a scientific work. In writing scientific papers, writing citations and managing journal references are important. This study aims to provide students with skills improvement in writing citations and managing journal articles as references for writing scientific papers using PAPALE (Mendeley Practical Guide). A total of 120 students from three classes were selected purposively because they were taking courses that required academic writing. The training was carried out through an interactive workshop approach divided into four stages: preparation, theory delivery, direct practice, and evaluation and feedback. The evaluation results showed a significant increase in students' technical skills, with 87% being able to insert citations and compile bibliographies automatically, and 79% showing an understanding of thematic reference management. The average pretest score of participants was in the range of 19 - 29 and increased to 86 - 95 in the posttest. The level of satisfaction with the training was very high, with an average score between 93.2 and 99.5. Participant comments revealed that the training succeeded in overcoming initial difficulties in using Mendeley, building self-confidence, and facilitating the process of writing scientific papers. These findings indicate that PAPALE training is effective in equipping students with essential competencies in digital management of academic citations and references.